A Novel Risk Predictive Scoring Model for Predicting Subsequent Infection After Carbapenem-Resistant Gram-Negative Bacteria Colonization in Hematological Malignancy Patients - Wu, Qiuling; Qian, Chenjing; Yin, Hua; Liu, Fang; Wu, Yaohui; Li, Weiming; Xia, Linghui; Ma, Ling; Hong, Mei (Frontiers in Oncology, 2022)
Background: To investigate the high-risk factors associated with the increased vulnerability for subsequent clinical CR-GNB infection in Carbapenem-resistant Gram-negative bacteria (CR-GNB) colonized hematological malignancies (HMs) patients, and build a statistical model to predict subsequent infection. Method: All adult HMs patients with positive rectoanal swabs culture for CR-GNB between January 2018 and June 2020 were prospectively followed to assess for any subsequent CR-GNB infections and to investigate the risk factors and clinical features of subsequent infection. Results: A total of 392 HMs patients were enrolled. Of them, 46.7% developed a subsequent clinical CR-GNB infection, with 42 (10.7%) confirmed infection and 141 (36%) clinically diagnosed infection. Klebsiella pneumoniae was the dominant species. The overall mortality rate of patients colonized and infected with CR-GNB was 8.6% and 43.7%. A multivariate analysis showed that remission induction chemotherapy, the duration of agranulocytosis, mucositis, and hypoalbuminemia were significant predictors of subsequent infection after CR-GNB colonization. According to our novel risk predictive scoring model, the high-risk group were ＞3 times more likely to develop a subsequent infection in comparison with the low-risk group. Conclusion: Our risk predictive scoring model can early and accurately predict subsequent CR-GNB infection in HMs patients with CR-GNB colonization. Early administration of CR-GNB-targeted empirical therapy in the high-risk group is strongly recommended to decrease their mortality.